Hubungan Tingkat Pengetahuan Mahasiswi STR Kebidanan Tanjungkarang Tentang Dismenorea Dengan Penanganan Nyeri Haid - Putriana, Yeyen; Sulistianingrum, lely (MIDWIFERY JOURNAL, 2024)
Background ; Menstruation and dysmenorrhea are concomitant events that occur every month in normal, adult women. Student learning activities can be disrupted due to abdominal pain or dysmenorrhoea. Appropriate initial treatment for students can overcome discomfort and can increase student productivityObjective: The aim of this research is to determine the relationship between level of knowledge and behavior in the initial treatment of dysmenorrhoea.Method: The research used a descriptive correlation research design with a cross sectional approach. The sampling used in this research was a probability sampling technique with a stratified sampling type. The number of samples in this study was 82 respondents, the data collection technique used a questionnaire. Data processing and bivariate analysis using chi square test with alpha 5%Results: The level of knowledge of female students regarding dysmenorrhoea was 82 respondents, the level of good knowledge was 60% of respondents, sufficient knowledge was 40% and the level of knowledge was poor (20%). The level of pain experienced by respondents was 22.5% moderate, 51% severe and 58% mild. 75% of respondents' initial handling behavior carried out appropriate behavior to treat dysmenorrhoea. . The results of this study show that there is a relationship between dysmenorrhoea and dysmenorrhoea handling behavior in female students of the Tanjungkarang Midwifery STR study program.Suggestion ; It is necessary to provide education to female students and assistance so that they can get through menstruation and dysmenorrhoea safely and comfortably. To stay healthy and follow PBM properly during menstruation and dysmenorrhea. Keywords: Dysmenorrhoea, level of knowledge, initial treatment behavior, Midwifery STR students Class of 2023